Memahami Proses Komunikasi Kelompok Pecinta Ayam Jago Aduan di Kawasan Manyaran - Setiawan, Lucky (Jurnal The Messenger, 2014)
Lucky Setiawan, G.331.09.0034. Understanding the Communication Process of Rooster Fighting Lover Group in Area Manyaran. Thesis: Study Program S-1 Communication Study University of Semarang. This study aims to determine the communication process conducted in a group of Rooster Fighting Lover in western region of Semarang. In addition, it also learns the group communication process with people outside of this community. The research method used is descriptive qualitative research method by describing the characteristics of the individual and the situation of a certain group. This study is simple that does not require a complicated theoretical basis or filing certain hypotheses. It is used the technique of collecting data through interviews and observations. It is concluded that in the process of communication that exist within this group, all members adhere only to a person who is considered as a senior. In addition the communication process of the group in responding protests outside is considered extreme. The group will not pay attention to the people comments.